Indonesian Case on Illegal Migrant - Ariadno, Melda Kamil (Indonesian Journal of International Law, 2012)
Indonesia has faced the problem of illegal immigrants for a long time, especially with the rise of war in other countries or other forms of oppression against a party who then makes them leave the country with the hope to live in another country better off than where they originated. The issue of "illegal migrants" itself has gained a lot of international attention as well as international talks that discussed the problem and how to overcome it. Policies and mitigation measures carried out so far can not address the problem of illegal immigration effectively, which force Government of Indonesia to accommodate those who are awaiting receipt of the status of refugees ("Refugee") and the opportunity to leave to Australia. It requires comprehensive and effective arrangements in tackling this includes identifying relevant agencies that should cooperate in the supervision and law enforcement action